Kontribusi Penyadapan Getah Pinus (Pinus Merkusii) terhadap Tingkat Pendapatan di PT. Inhutani I Kabupaten Gowa, Sulawesi Selatan - Herawaty Herawaty; Nurul Mukhlishah; Faizah Mahi; Agus Salim Syam (Publikasi Indonesia, 2022)
Income is a person's source of income to meet daily needs which are very important for survival. The income of pine sap tappers who live in rural areas generally does not come from one source, but comes from two or more sources of income. The relatively low level of income requires household members who are potential farmers to work harder. This study was to determine the contribution of tapping pine sap to the income level of the tapping community at PT. Inhutani I, Gowa Regency, South Sulawesi. This research was conducted from April to May 2022. The method used was the census method. The number of samples consisted of 20 heads of families with pine sap tappers status. This study uses primary data and secondary data. Collecting data through field surveys and data collection techniques using observation, interviews and questionnaires. The data analysis used in this research is qualitative and quantitative analysis. The results showed that the average income of pine resin tappers in the pine forest area. Pine sap income Rp. 2.030.000/month, other sector income Rp. 1.365.000/month, and the total income of the tappers is Rp. 3.395.000/month. Then the total income of pine resin tappers is Rp. 3.395.000/month, the contribution of pine resin tappers is 59.79%/month. With pine resin income of Rp. 2.030.000/month, people in pine forest area. And the income contribution of tappers is Rp. 1.745.000/month, or 59.79% with a total income of Rp. 3.395.000/month, and the components needed for tappers are Rp. 1.650.000/month. The need for direction and guidance from PT. Inhutani I Gowa to the community to be enthusiastic and participate in increasing the production of pine resin in order to meet the set targets, and this is useful for the company because the production of sap increases, the income of the community also increases.